Epidemiology of Malignant Cervical, Corpus Uteri and Ovarian Tumours – Current Data and Epidemiological Trends - Waldmann, A.; Eisemann, N.; Katalinic, A. (Geburtshilfe und Frauenheilkunde, 2013)
Cervical, uterine and ovarian cancers are the most common malignancies of the female genital tract. Using current data from population-based cancer registries in Germany, we present the recent figures for the incidence, prevalence, associated mortality and survival for these cancers. In 2009, a total of 23 800 women were newly diagnosed with one of the three gynaecological cancers (cervical cancer: 20.3 %, endometrial cancer: 48.5 %, ovarian cancer: 31.2 %). This figure equals approximately one third of the number of women newly diagnosed with breast cancer in the same year. The relative 5-year survival for carcinomas of the corpus uteri is 79 % and is higher that those for cervical cancer (68 %) and ovarian cancer (40 %). Ovarian cancer in particular is often diagnosed at a later stage and has a high risk of recurrence. Due to the favourable prognosis for endometrial tumours and the unfavourable prognosis for ovarian malignancies, the incidence of various gynaecological tumours is ranked differently compared to the 5-year prevalence of these same tumours. Currently, the 5-year prevalence in Germany for patients with cervical, endometrial or ovarian cancer is estimated to be around 80 000 women. Slightly more than half of these women were diagnosed with cancer of the corpus uteri. Around 25 % of women have ovarian and 21 % have cervical cancer.
Keywords: ovarian cancer; cervical cancer; endometrial cancer; epidemiology